Depolarization shift in the resting membrane potential of inferior colliculus neurons explains their hyperactivity induced by an acoustic trauma - Hsiao, Chun-Jen; Galazyuk, Alexander V. (Frontiers in Neuroscience, 2023)
Introduction Neuronal hyperactivity has been associated with many brain diseases. In the auditory system, hyperactivity has been linked to hyperacusis and tinnitus. Previous research demonstrated the development of hyperactivity in inferior colliculus (IC) neurons after sound overexposure, but the underlying mechanism of this hyperactivity remains unclear. The main goal of this study was to determine the mechanism of this hyperactivity. Methods Experiments were performed on CBA/CaJ mice in a restrained, unanesthetized condition using intracellular recordings with sharp microelectrodes. Recordings were obtained from control (unexposed) and unilaterally sound overexposed groups of mice. Results Our data suggest that sound exposure-induced hyperactivity was due to a depolarizing shift of the resting membrane potential (RMP) in the hyperactive neurons. The half width of action potentials in these neurons was also decreased after sound exposure. Surprisingly, we also found an RMP gradient in which neurons have more hyperpolarized RMPs with increasing depth in the IC. This gradient was altered in the overexposed animals.